Carbon Nanotubes for Targeted Drug Delivery - Hasnain, Md Saquib; Nayak, Amit Kumar (SpringerBriefs in Applied Sciences and Technology,, 2019)
This book provides a detailed introduction to carbon nanotubes (CNTs) for targeted drug delivery. After a brief overview of the classification, preparation, and characterization of carbon nanotubes, it focuses on their use in targeted drug delivery. It presents CNTs for brain targeting, ocular targeting, cancer targeting, and lymphatic targeting, as well as antibody therapy. The book also includes chapters on carbon nanotubes for controlled drug delivery, transdermal drug delivery, solubility enhancement, vaccine delivery, gene delivery, and as quantum dots. Last but not least, it addresses the absorption and transportation of CNTs, toxicity and regulatory considerations, as well as clinical trials and the market status of CNTs. .